A systematic review of plant extracts and secondary metabolites of tick-killing interest for Rhipicephalus microplus in cattle (Revista Sistemas de Producción Agroecológicos, 2024)
The current problems in livestock production, related to the lack of effective pest control, especially ticks, have caused a significant drain on resources and production. This situation highlights the need to explore natural and sustainable alternatives for pest management in the livestock sector. A structured systematic review was carried out using the PRISMA protocol, on plant extracts and identification of secondary metabolites of the same for acaricidal purposes, specifically on Rhipicephalus microplus ticks. The search for information was based on five scientific platforms: Elsevier, PubMed, Scielo, Springer and ResearchGate. This review documented different analyses on studies with tickicidal purposes using extracts from different plants. Within the information collected from articles published in the last 10 years, 104 articles were identified, where 178 investigated plants belonging to 60 families were cited. The Asteraceae family is mostly studied for acaricidal purposes. In addition, it was identified that the extract of the Lobelia leschenaultiana plant has the lowest acaricidal concentration (0.004%, 93.33% mortality); and the Acmella oleracea plant has been the most effective as a larvicide (0.31%, 100% larval mortality). These results offer detailed knowledge about the efficacy of various plant extracts and their groups of secondary metabolites regarding their tick-killing potential, which is important in the control of R. microplus in cattle farms. Most acaricidal studies with plant extracts reach in vitro studies; it is necessary to carry out these studies in situ conditions, in this way to consider therapeutic alternatives based on plants to be successfully linked to the comprehensive control of R. microplus in cattle farms.
Keywords: phytochemistry; phytotherapeutics; therapeutic alternative